Evaluation of soft tissue in class III cases treated by different types of face masks - Barmpoutis, Panagiotis (My University, 2006)
İSKELETSEL TİPLERDE YÜZ MASKESİ İLE TEDAVİ EDİLMİŞ OLAN SINIF ııı OLGULARDA YUMUŞAK DOKU ANALİZİ İskeletsel Sınıf III maloklüzyon en zor tedavi edilen maloklüzyonlar arasındadır. Sınıf III maloklüzyon, maksiller retrognati, mandibuler prognati veya her ikisinin karışımı olarak karşımıza çıkabilmektedir. Bir çok araştırıcı, Sınıf III vakalarının çoğunun maksiller retrognatiye bağlı olarak oluştuğundan bahsetmiştir. Bu bulgu yüz maskesini en önemli tedavi araçlarından biri haline getirmektedir. Estetiğin, ortodonti hastalarının pek çoğu için motivasyon kaynağı oluşturduğu ve profil güzelliğinin de yüz estetiğinde çok önemli bir yere sahip olduğu göz önünde bulundurulunca; iki farklı yüz maskesi tipi ile tedavi edilmiş iki grup Sınıf III vakalarında meydana gelmiş olan yumuşak doku profil değişikliklerini incelemeye karar verdik. Çalışmada kullanılan materyal Marmara Üniversitesi, Dişhekimliği Fakültesi, Ortodonti AD arşivinden seçilmiştir. Bölümümüzde iki farklı yüz maskesi tipi ile tedavi edilmiş olan Sınıf III hastalar kullanılmıştır. Birinci grup Petit tip yüz maskesi ile tedavi edilmiş, yaş ortalaması 12.1 ve tedavi süresi 6 ay olan 12 hastadan oluşturulmuştur. İkinci grup yine ortalama yaşı 12.7 olan, MMPH ile ortalama 6 ay boyunca tedavi edilmiş olan 12 hastadan meydana gelmiştir. Bütün yumuşak doku analiz ölçümleri Yeditepe Üniversitesi, Dişhekimliği Fakültesi, Ortodonti AD bulunan Dolphin Imaging System kullanılarak yapılmıştır. Her iki aygıtın da yumuşak doku profili üzerinde anlamlı etkileri olduğu görülmüştür. İki grubun karşılaştırılmasında farkların anlamlı olduğu bulunmuştur. EVALUATION OF SOFT TISSUE IN CLASS III CASES TREATED BY DIFFERENT TYPES OF FACE MASKS The skeletal Class III malocclusion is one of the most difficult malocclusions to treat. A Class III malocclusion may be seen with maxillary retrognathism, mandibular prognathism, or combination of both. Many researchers have mentioned that most of the Class III cases are due to maxillary retrognathism. This finding makes the face mask one of the most important treatment modalities. Taking into consideration that esthetics is a basic motivation for most orthodontic patients and considering that profile beauty takes an important place in facial esthetics we decided to evaluate the soft tissue profile changes of two groups of Class III cases treated with two different types of face masks. The material of the study was collected from the archive of the Department of Orthodontics of Marmara University, Shcool of Dentistry. We used Class III patients that were treated with two different types of face mask in our department. First group consisted of 12 patients and these were treated with petit type face mask (Classical Type face mask). The average age of this group was 12.1 years old and the duration of the treatment was 6 months. Our second group consisted of 12 patients with an average age of 12.7 years old. These patients were treated with MMPH (Maxillary Modified Protraction Headgear) for 6 months in average. All the measurements for soft tissue analysis will be done by using the Dolphin Imaging System from the Yeditepe University, School of Dentistry, Department of Orthodontics. Both appliances had a significant effect on the soft tissue profile. When two groups were compared, differences were found to be significant.
Keywords: Diş Hekimliği_Tedavi; Ortodonti